Regulation of anti-tumor immunity by metal ion in the tumor microenvironment - Gao, Yaoxin; Liu, Shasha; Huang, Yifan; Li, Feng; Zhang, Yi (Frontiers in Immunology, 2024)
Metal ions play an essential role in regulating the functions of immune cells by transmitting intracellular and extracellular signals in tumor microenvironment (TME). Among these immune cells, we focused on the impact of metal ions on T cells because they can recognize and kill cancer cells and play an important role in immune-based cancer treatment. Metal ions are often used in nanomedicines for tumor immunotherapy. In this review, we discuss seven metal ions related to antitumor immunity, elucidate their roles in immunotherapy, and provide novel insights into tumor immunotherapy and clinical applications.